Impact of water stress and nitrogen fertilization on growth, biochemical changes and carbon assimilation of commercial strawberry (Fragaria x ananassa Duch.) planted in East Java, Indonesia - Yenni (2021)
Strawberry has a nutritional content that is beneficial to the human body. In Indonesia, the cultivation of this plant has met with challenges due to climate change. Water stress is one of the climate changes that affect the growth and quality of strawberries. This research was carried out to determine the impact of water stress and nitrogen fertilization on growth, biochemical changes, and carbon assimilation of strawberries. This study was conducted in a glasshouse at the Indonesian Citrus and Subtropical Fruit Research Institute, East Java Indonesia, from June 2018-January 2020. All experiments were arranged in randomized complete block design (RCBD) with three replications. In accomplishing the research, four experiments were carried out. In the first experiment, three cultivars of strawberry (C1=Earlibrite, C2=California, C3=Sweet Charlie and four water stress levels (W1= 100% field capacity (FC), W2=75% FC, W3=50% FC, W4=25% FC) were used to determine the best cultivar under different levels of water stress. The results showed that total chlorophyll and anthocyanin contents were influenced by the interaction effects of cultivars and water stress (WS). WS decreased plant growth, chlorophyll content, leaf gas exchange, leaf relative water content, length, diameter, and weight of fruit but enhanced total soluble solid, anthocyanin, and proline contents. Among the cultivars, California strawberry had highest flowers and fruits number, and anthocyanin content. Hence, this cultivar is recommended to be planted under WS. For the second experiment, two levels of WS (W1=100% FC, W2=75% FC) and four irrigation intervals (II) (F1=daily irrigation; F2 (2 days II); F3 (4 days II); F4 (6 days II) were used to investigate the effect of WS and II on strawberries. The results indicate that W2F4 caused lower growth, yield, chlorophyll content, and leaf gas exchange, but higher water use efficiency (WUE), proline content and fruits total sugar. Increasing WUE and proline indicate that the strawberry plant can adapt (tolerant) to water stress. Therefore, II can be used as a strategy to vegetate strawberries in the dry season. In the third experiment, four fertilizer sources (P1=without fertilizer, P2=NPK fertilizer, P3=dry goat dung fertilizer, P4=½ NPK+½ dry goat dung fertilizer and WS (W1=daily irrigation 100% FC; W2=2 days II 75% FC; W3=6 II 75% FC) were used to determine the best fertilizer source for the growth, biochemical changes and carbon assimilation of strawberries. It was observed that the interaction of different water stress and fertilizer types had significant effect on all parameters except for the total sugar in strawberry fruits. The application ½ NPK + ½ goat dung fertilizer resulted in higher of plant height, leaves number, biomass, chlorophyll content, sugar content, transpiration rate, photosynthesis rate, and NPK content. Plants that were not fertilized had the lowest growth compared to those fertilized. In the last experiment, five nitrogen fertilizer rates (N1=without N fertilizer, N2=46 kg N/ha, N3 = 92 kg N/ha, N4 = 138 kg N/ha, N5 = 184 kg N/ha) and WS levels (W1=daily irrigation 100% FC; W2=2 days II 75% FC; W3=6 days II 75% FC) were used to determine the best nitrogen fertilizer rate on strawberries. The results showed that strawberry plants subjected to WS and low or no nitrogen fertilizer application had a decline in growth and yield. WS increased WUE and nitrogen use efficiency (NUE) of strawberry plant. Nitrogen increased the growth, chlorophyll, leaf gas exchange, ANR, proline, and yield components of the strawberry under WS. From this research, it can be concluded that the application of nitrogen fertilizer under WS was able to mitigate the negative effect of water stress by maximizing WUE and NUE on the strawberry plants.